Stress, a reflective self and an internal locus of control: On the everyday clinical placement experiences of older undergraduate radiographers in the UK. Issue 1 (February 2022) - Mawson, J.A.; Miller, P.K.; Booth, L.
Abstract: Introduction: Extant evidence indicates that the stresses experienced by younger undergraduate radiographers and their older counterparts vary considerably. Much of this difference has, however, emerged from analyses of the academic component of a radiography degree whereas little work has focused to date upon the specific business of clinical placement. Given this, the research herein reports findings from a qualitative study of how older undergraduate radiography students in the UK assemble their stress and stressors around clinical placement. Methods: An Interpretative Phenomenological Analysis was employed. N = 6 older undergraduate students undergoing their final year placement were purposively recruited from a variety of hospitals. With full institutional ethical approval, a semi-structured interview was conducted with each participant. Results: Four superordinate themes emerged. These were: (1) Self-identity and perceived competence; (2) Understaffing, instability and affect; (3) Episodic experience and feeling 'thrown-in'; (4) Unpreparedness for the challenging patient. Critically, each theme describes an interaction between stressor, experience of stress and self. Conclusion: While familiar stressors were apparent, the older participating students actively made sense of them in terms of their manageability. This provides a strong contrast with existing literature, which tends to imply a more externalised locus of control among (largely younger) students. Implications for practice: Stress in the NHS is a continuing issue and there is a clear rationale for further investigation to ascertain the level of clinical support available and to determine whether further improvements could assist students on clinical placement. Collaboration between academic institutions and clinical sites would allow open discussion around clinical stress experienced by radiography students, with locus of control a potential point of focus, fostering a proactive partnership approach to stress-management and identification of difficulties before they exacerbate.